LRRC3B Polymorphisms Contributed to Breast Cancer Susceptibility in Chinese Han Population - Wang, Yuxin (Frontiers in Oncology, 2021)
Purpose: LRRC3B gene, as a tumor suppressor gene was involved in the development and progress of breast cancer (BC). However, the effect of LRRC3B polymorphisms on BC has rarely been reported. In the study, we aimed to evaluate the relation between LRRC3B variants and BC risk. Methods: Among 563 BC patients and 552 healthy controls, ten single-nucleotide polymorphisms (SNPs) in LRRC3B were genotyped by Agena MassARRAY. Odds ratios (OR) and 95% confidence interval (CI) were calculated using logistic regression model. Results: Our study demonstrated that rs1907168 polymorphism (heterozygous: OR = 0.71, p = 0.017) was related to the reduced risk of BC in the overall. In stratified analyses by age, rs1907168 was associated with the decreased (heterozygous: OR = 0.53, p = 0.002) while rs78205284 (homozygote: OR = 2.83, p = 0.034) increased BC susceptibility among the population at age ≤ 51 years. Rs6551122 (recessive: OR = 0.51, p = 0.028) and rs12635768 (homozygote, OR = 0.36, p = 0.023) polymorphisms were related to the smaller BC tumor size (< 2cm). In addition, rs112276562 (heterozygote OR = 0.56, p = 0.002), rs6551122 (heterozygote OR = 0.63, p = 0.016) and rs73150416 (heterozygote OR = 0.57, p = 0.005) variants contributed to the lower incidence of PR-positive BC. Moreover, rs6788033 was associated with a lower the expression level of Ki-67 (log-additive: OR = 0.68, p = 0.024). Furthermore, we found that the association of ‘GATT’ haplotype with an increased risk for BC. In addition, LRRC3B gene was down-regulated in BC tumor and had a poor prognosis in BC in silico analysis. Conclusion: Our study firstly found LRRC3B SNPs contributed to the risk of BC, suggesting LRRC3B variants might help to predict BC progression.